CRISPR-Based Gene Editing in Human and Animal Health: Revolutionizing Disease Resistance and Treatment - Bandar Aloufi (Journal of Pure and Applied Microbiology, 2026)
CRISPR gene-editing technology has revolutionized modern genetics, offering precise and efficient modifications across multiple domains, including human medicine, agriculture, and veterinary science. This study explores the diverse applications of CRISPR, highlighting its role in treating genetic disorders such as sickle cell anemia and Duchenne muscular dystrophy, advancing cancer immunotherapies, and developing CRISPR-based antiviral therapies for HIV and COVID-19. In agriculture, CRISPR has facilitated the development of disease-resistant livestock, enhanced crop yields, and improved food sustainability. Additionally, CRISPR is being integrated with artificial intelligence (AI) and bioinformatics to optimize gene-editing accuracy, predict off-target effects, and accelerate drug discovery. Despite these advancements, CRISPR faces significant challenges, including ethical dilemmas surrounding germline editing, regulatory inconsistencies across countries, high costs of gene therapies, and concerns about genetic inequality. The legal and social implications of CRISPR remain complex, requiring global cooperation to establish standardized regulations and ensure equitable access to genetic therapies. Emerging innovations such as base editing, prime editing, and epigenetic modifications offer promising solutions to improve CRISPR’s precision and safety. Looking ahead, CRISPR’s long-term success will depend on responsible scientific advancements, ethical oversight, and public acceptance. With the continued refinement of gene-editing techniques and AI-driven CRISPR optimizations, this technology holds the potential to revolutionize medicine, agriculture, and environmental conservation. However, careful implementation and transparent discussions are essential to navigate the ethical, legal, and societal challenges that accompany CRISPR’s rapid development.